2021
DOI: 10.1111/jam.14978
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of the lectin from pomegranate sarcotesta (PgTeL) against Listeria monocytogenes

Abstract: Aims: To investigate the effects of the lectin from Punica granatum sarcotesta (PgTeL) on growth, viability, cell structure, biofilm formation and chitinase activity of Listeria monocytogenes. In addition, the effect of PgTeL on the adhesion and invasion of human cells (HeLa) was determined. Methods and Results: PgTeL showed bacteriostatic and bactericidal effects on the strains L. monocytogenes N53-1 and EGD-e, causing morphometric alterations, cell aggregation, strong deformation and cell disruption. PgTeL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the present study, the MIC of moringin against L. monocytogenes was 400 μM (0.124 mg/ml; Table 2 ). Compared to that of phenyllactic acid (1.25 mg/ml; Ning et al, 2017 ) and the lectin from pomegranate sarcotesta (0.0125 mg/ml; Silva et al, 2021 ), moringin showed a moderate inhibitory effect against L. monocytogenes . Moringin is one of the isothiocyanates.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the MIC of moringin against L. monocytogenes was 400 μM (0.124 mg/ml; Table 2 ). Compared to that of phenyllactic acid (1.25 mg/ml; Ning et al, 2017 ) and the lectin from pomegranate sarcotesta (0.0125 mg/ml; Silva et al, 2021 ), moringin showed a moderate inhibitory effect against L. monocytogenes . Moringin is one of the isothiocyanates.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, agglutination assays showed that Lm reacts to different plant lectins in a strain-specific manner (Facinelli et al, 1998;Slifkin & Doyle, 1990). However, lectins of Canavalia ensiformis and Punica granatum have antibiofilm activities against Lm and other bacteria (Jin et al, 2019;Silva et al, 2021). This suggests that lectins of some plant species may limit adhesion to their surface.…”
Section: Lm Attachment To Plantsmentioning
confidence: 99%